2013
DOI: 10.1007/s10147-013-0579-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative diagnosis of lymph node metastasis by transcription–reverse transcription concerted reaction assay in gastric cancer

Abstract: The TRC assay method using lymph node washings is a rapid, simple genetic diagnosis with greater sensitivity than conventional diagnosis by H&E staining of permanent specimens, and enables conservation of lymph nodes in toto as permanent specimens. This TRC method would enable rapid diagnosis even in town hospitals where no pathologist is ordinarily stationed, and is considered to contribute to the clinical application of the sentinel node theory of gastric cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Therefore, sensitive and accurate detection methods, such as IHC or reverse transcription polymerase chain reaction (RT-PCR), should be used to detect micrometastasis of SSLNs in AGC. Studies have reported that rapid, sensitive IHC and RT-PCR can detect micrometastases in a few minutes (Lee et al, 2012;Hirayama et al, 2014). If true, then the value of the SSLN tracing technique for individual lymphadenectomy of AGC will be more significant.…”
Section: Characteristics Of Ssln Tracing For Advanced Gastric Angle Cmentioning
confidence: 99%
“…Therefore, sensitive and accurate detection methods, such as IHC or reverse transcription polymerase chain reaction (RT-PCR), should be used to detect micrometastasis of SSLNs in AGC. Studies have reported that rapid, sensitive IHC and RT-PCR can detect micrometastases in a few minutes (Lee et al, 2012;Hirayama et al, 2014). If true, then the value of the SSLN tracing technique for individual lymphadenectomy of AGC will be more significant.…”
Section: Characteristics Of Ssln Tracing For Advanced Gastric Angle Cmentioning
confidence: 99%